The End of All Things: Geomateriality and Deep Time - Toadvine, Ted (Investigaciones Fenomenológicas, 2021)
The world, as a unifying nexus of significance, is inherently precarious and constitutively destined toward its own unraveling. Our fascination with a future end of the world masks our realization that the world as common and unified totality is already disintegrating. What remains after the end of the world is also what pre-cedes it, the geomaterial elements, which condition the world without being reducible to things within it. Through our participation in elemental materiality, we encounter the abyssal vertigo of deep time as an anachronistic rupture of lived and historical time. The geological memory of stone situates it at the threshold of world and non-world, while our liability to an immemorial prehistory situates us at the intersection of incommensurable durations, those of the ancestral past as well as the apocalyptic future. El mundo, como un nexo de significado unificador, es intrínsecamente precario y está constitutivamente destinado a su propio desenredo. Nuestra fascinación por un futuro final del mundo enmascara nuestra comprensión de que el mundo como totalidad común y unificada ya se está desintegrando. Lo que queda después del fin del mundo es también lo que lo precede, los elementos geomateriales, que condicionan el mundo sin ser reducibles a las cosas dentro de él. A través de nuestra participación en la materialidad elemental, nos encontramos con el vértigo abismal del tiempo profundo como una ruptura anacrónica del tiempo vivido e histórico. La memoria geológica de la piedra lo sitúa en el umbral del mundo y del no mundo, mientras que nuestra responsabilidad ante una prehistoria inmemorial nos sitúa en la intersección de duraciones inconmensurables, tanto del pasado ancestral como del futuro apocalíptico.